2000
DOI: 10.1001/archpedi.154.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Symptoms of Gastroesophageal Reflux During Childhood

Abstract: Symptoms suggestive of GER are not rare in childhood, yet only a fraction of children with symptoms are treated with over-the-counter antacids or histamine2 antagonists. Prospective longitudinal data are needed to determine which children with symptoms of GER actually have GER disease and are at risk of developing complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
1
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(161 citation statements)
references
References 8 publications
3
148
1
9
Order By: Relevance
“…Comparisons with a similar-aged typically developing population 24 showed a higher prevalence of GER.…”
Section: Gastrointestinal Disordersmentioning
confidence: 78%
“…Comparisons with a similar-aged typically developing population 24 showed a higher prevalence of GER.…”
Section: Gastrointestinal Disordersmentioning
confidence: 78%
“…Gastroesophageal reflux (GER) which frequently occurs in otherwise healthy infants, refers to reflux without associated complications, and it generally resolves between 1-2 years of age (4,27). GERD is defined by the presence of reflux in combination with associated complications, and usually does not resolve spontaneously (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, it is important to make a distinction between GER and GERD. Since GERD symptoms are usually age-dependent and heterogeneous during childhood, it could be useful for clinicians to be able to assess the severity of esophagitis based on the presenting symptoms (4,27,30). In adults, several studies investigating the relationship between the symptoms and endoscopic findings of GERD reported a poor correlation (31-34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children aged 2-12 years, the main symptoms include regurgitation, vomiting, abdominal pain and feeding difficulties, but typical GER symptoms can be reliably assessed in children 8-12 years of age [11]. Nelson et al have shown how the GERD symptoms can vary depending on the age of the patient (Table 1) [3]. Table 1.…”
Section: When To Suspect Gerd?mentioning
confidence: 99%